Mycobacterium chelonae hand infection following acupuncture: a case report and literature review - Matic, Sladjana; Teodosic, Valerija; Zagorac, Slavisa (Frontiers in Medicine, 2024)
Infection of the hand due to atypical mycobacteria is an uncommon condition. We present a case of hand infection caused by Mycobacterium chelonae in a patient who had undergone acupuncture. The clinical features, treatment, and outcome are described. Biopsy and cultures are essential for diagnosis as Mycobacterium chelonae is a rare cause of human infection and is difficult to diagnose unless suspected. The patient was successfully treated with surgical excision, debridement, and antimicrobial therapy. We reviewed the available literature to summarize the experience with this infectious entity.